If it's not what You are looking for type in the equation solver your own equation and let us solve it.
8)6x+1=7x+11
We move all terms to the left:
8)6x+1-(7x+11)=0
We add all the numbers together, and all the variables
8)6x+1-(7x=0
| 8x-15=-2x+25 | | 2x+7=27÷2 | | 5x-3x-15=7+4+3x | | √x=10−4 | | n2+201n-2700=0 | | 6y+12=3y+6 | | 2u-1=4u-19 | | x+5-14=16 | | 7h+8=76 | | X-1÷2=x-2÷3-3-x÷4 | | 25=a-295 | | 2s-23=9s+12 | | X-1÷2=x-2÷3=3-x÷4 | | 10x-37=4x-6 | | 3x-16=-2x-41 | | 2o+4=5o+13 | | 204=w-11 | | 8x+4=5x-17 | | 5-2n=10+3 | | t+11=145 | | 4l-16=3l-16 | | √n+2=9 | | 2000=c/5 | | 6x+16=4x+9 | | 10i-29=4i-5 | | m(2)/2=25 | | m(2)/2=25,m=7 | | 2h+3=5h-21 | | -5x-8=-x-24 | | 4y=5+3y | | 6e+1=3e+19 | | 2t=7-5t |